(3fXe EVGAI GdCOehS aj eUWdM GdbGehSs - (3SjO eMeO Hf SjO YHO Gddg Hf GdMGL EHQGgje GdYdhjs; (3GdgdGdj , CHh GdYHGS CMeO Hf YHO GdYRjR Hf GdQTjO GdgdGdj GdSLdeGSj,J (B1175 (3g` s ((3ehQjJGfjG s)
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje bGd SjO eMeO Hf SjO YHO Gddg Hf GdMGL EHQGgje MeOkG def CfWbg HGdHjGf cd aUjM Pdb GddSGf hNUfG HGdYQHjI GdHGOi CaUM ef aGg HMQa GdVGO s
(3BNQgG (B:s
(3heG Ydi aYGdI Ef GTJed Ydi ShGg cSQhg MjK Md hgcPG GdaYGd cGdMRGe hcGdYeGeI hcGdNJGe CfgjJ eG bUOJg HMhd hbhI Gddg GdYXje GdWhd s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B151 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B275s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI SjFI s
(3GdfSNI HgG JdhjK , CQVg s
Keywords: (3GddZIs